All Days 1993
DOI: 10.2118/25494-ms
|View full text |Cite
|
Sign up to set email alerts
|

Stimulating Weak Formations Using New Hydraulic Fracturing and Sand Control Approaches

Abstract: This paper discusses particular aspects critical to designing a successful fracturing treatment for higher permeability reservoirs with the objectives of stimulation anellor sand control. The process entails creating a short and wide fracture and packing it with multiple layers of proppant, possibly incorporating a. resin-coateQ proppant.Use of a reservoir simulator to predict or history match a pressure drop profile throughout a given drainage area will be presented. A fracture length can be determined from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…These causes of sand failure and production are well documented in the industry. 2,3,4,5 Opportunity Assessment In general, the field maintained a high production rate; however, later in the field's productive life, productivity declined due to excessive gas, sand, and water production. As of the end of February in 1999, 44% (57 strings) of the total production strings were idle with estimated locked-in potential of 14.1 thousand STB/D.…”
Section: Initial Completion Philosophymentioning
confidence: 99%
“…These causes of sand failure and production are well documented in the industry. 2,3,4,5 Opportunity Assessment In general, the field maintained a high production rate; however, later in the field's productive life, productivity declined due to excessive gas, sand, and water production. As of the end of February in 1999, 44% (57 strings) of the total production strings were idle with estimated locked-in potential of 14.1 thousand STB/D.…”
Section: Initial Completion Philosophymentioning
confidence: 99%
“…4 Despite undoubted success, frac&pack technology is still lacking to achieve optimum completion efficiency and to deliver reliably the production as designed. Many studies have shown that frac&pack is significantly different from low-perm fracturing regarding completion fluids, 5,6 rock mechanics, 7,8 pressure analysis, [9][10][11][12] treatment design and execution. [13][14][15][16] Unfortunately, current practices do not always pay attention to these differences and sometimes copy the techniques and operational procedures originally developed for traditional fracturing.…”
Section: Introductionmentioning
confidence: 99%
“…4 Despite undoubted success, frac&pack technology is still lacking to achieve optimum completion efficiency and to deliver reliably the production as designed. Many studies have shown that frac&pack is significantly different from low-perm fracturing regarding completion fluids, 5,6 rock mechanics, 7,8 pressure analysis, [9][10][11][12] treatment design and execution. [13][14][15][16] Unfortunately, current practices do not always pay attention to these differences and sometimes copy the techniques and operational procedures originally developed for traditional fracturing.…”
Section: Introductionmentioning
confidence: 99%